The Politics and Economics of Technology: Bankside Power Station and the Environment, 1945–81. (4th May 2019) - Murray, Stephen
Abstract : Bankside B power station was a controversial post-war addition to London's cityscape: objections centred on its adverse visual and environmental impact on a sensitive riverside site opposite the City of London. This article argues that an array of state agencies espoused technology as the solution to Bankside's amenity, pollution and energy-efficiency issues. However, there were tensions and conflicts between the solutionism of actors proposing — and imposing — such technology and the pragmatism of those organisations which had to implement and operate, or reject, these proposals. The key consideration for the electricity industry was the provision of an abundant, timely and cost-effective energy supply. Technology ameliorated the environmental impact of the station but engendered adverse long-term issues. From the late 1950s the pollution from Bankside became increasingly intolerable in the context of London's improved air and river quality; yet economic factors precluded further technological mitigation solutions prior to the station's closure in 1981.